False documents : inter-American cultural history, literature, and the lost decade (1975-1992) - Weiser, Frans (Global Latin/o Americas., 2020)
""Examines the work of writers and journalists from Hispanic America, Brazil, and the US from the 1970s to 1990s who appropriated history as a tool for repositioning democracies in a hemispheric context in order to expose how governments controlled and misrepresented events"--Provided by publisher"--